Family medicinal plants (toga) in Tanap village Sanggau regency and their utilization by the Dayak Muara ethnic for the treatment of digestive system disorders - Fathul Yusro; Evy Wardenaar; Yeni Mariani (Universitas PGRI Semarang, 2022)
Medicinal plants are used for various kinds of health care, one of which is to treat problems in the digestive system. This research aimed to analyze the utilization of family medicinal plants (TOGA) by the ethnic of Dayak Muara in Tanap village in handling digestive system disorders. This study was conducted by survey method with a purposive sampling technique. This research was initiated by conducting interviews with the people of Tanap village who came from the Dayak Muara, then continued with identifying the medicinal plants mentioned. The data obtained were then analyzed with an ethnobotanical index in the form of Use Value (UV), Informant Consensus Factor (ICF), and Fidelity Level (FL). The Dayak Muara ethnic in Tanap Village uses 22 species of TOGA to handle digestive system disorders. The highest families used were Zingiberaceae and Amaryllidaceae. The dominant plant parts used, processing method, administration method, and remedies form for the handling of digestive system disorders are leaves (36%), boiled processing (43%), drinking (44%), and single herb form (67%). Plants with high use value (UV=1) are jambu biji (Psidium guajava) and kunyit (Curcuma longa). The digestive system disorder categories with the highest ICF included sprue (1), nausea and vomiting (0.98), intestinal worms, diarrhea, abdominal pain, and constipation (0.97). Plant that had the highest FL value (100%) included cocor bebek (Bryophyllum pinnatum), patah tulang (Euphorbia tirucalli), and putri malu (Mimosa pudica) for the treatment of toothache. Entawak (Artocarpus anisophyllus) for stomachache, pinang (Areca catechu) for constipation, lidah buaya (Aloe vera) for hemorrhoids, and sawo (Manilkara zapota) for stomachache.